HUBUNGAN ANTARA DUKUNGAN ORANG TUA DAN KEMAMPUAN BACAAN TAJWID SISWA DI SMP ISLAM KARAWANG - Hamada, Shabrina Putri; Taufik Mustofa; M. Makbul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the relationship between parental support and students’ tajwid reading ability at SMP Islam Karawang. The study used a quantitative correlational approach. The population consisted of 85 students, and 57 students who were able to read the Quran were selected through purposive sampling. Data were collected through a parental support questionnaire and a Quran reading practice test focused on makharijul huruf accuracy, tajwid rule application, and reading fluency. Data were analyzed using descriptive statistics and Pearson Product Moment correlation. The findings show that parental support was generally in the moderate category, with 41 students or 72% of respondents. Students’ tajwid reading ability was also in the moderate category, with 34 students or 60% of respondents. The Pearson correlation test produced a coefficient of 0.027 with a significance value of 0.840. Since the significance value was greater than 0.05, the alternative hypothesis was rejected. The result indicates no significant relationship between parental support and students’ tajwid reading ability at SMP Islam Karawang. These findings suggest that tajwid reading ability is likely influenced by other factors, such as learning motivation, reading practice intensity, teacher guidance, school learning quality, and students’ reading habits.